Exploring Presuppositions In Podcast Interviews: A Pragmatic Analysis Of Shawn Mendes' Narrative On Jay Shetty's Youtube Channel - Cindy Febryanis Gee; Atha Almisa Floren Agustina; Ananda Rizky; Mia Perlina (Indonesian Journal Publisher, 2025)
This study investigates the role of presuppositions in spoken media, focusing on podcast interviews, to understand how they shape audience perceptions. Presupposition, a concept in pragmatics, refers to implicit assumptions embedded in a speaker’s words, which are often accepted by listeners without question. This research applies Yule’s (1996) presupposition theory to a podcast episode featuring Shawn Mendes on Jay Shetty’s YouTube channel. Employing a descriptive qualitative methodology, the study categorizes six types of presuppositions: existential, factive, lexical, structural, non-factive, and counterfactual. The analysis highlights how these presuppositions structure Mendes' personal and professional narrative, guiding listeners' interpretations in real time. The study concludes that identifying presupposition types contributes to understanding the subtle ways spoken media influences audience engagement and narrative construction. This research provides insights into pragmatic analysis in digital spoken media, offering a foundation for further exploration in this dynamic field